1993
DOI: 10.1128/mcb.13.1.276
|View full text |Cite
|
Sign up to set email alerts
|

Acute-phase response factor, a nuclear factor binding to acute-phase response elements, is rapidly activated by interleukin-6 at the posttranslational level.

Abstract: Interleukin-6 (IL-6) is known to be a major mediator of the acute-phase response in liver. We show here that IL-6 triggers the rapid activation of a nuclear factor, termed acute-phase response factor (APRF), both in rat liver in vivo and in human hepatoma (HepG2) cells in vitro. APRF bound to IL-6 response elements in the 5'-flanking regions of various acute-phase protein genes (e.g., the %-macroglobulin, fibrinogen, and al-acid glycoprotein genes). These elements contain a characteristic hexanucleotide motif,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
376
0
4

Year Published

1995
1995
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 520 publications
(388 citation statements)
references
References 65 publications
8
376
0
4
Order By: Relevance
“…Previous several studies identified a highly conserved CTGG(G/A)AA motif in the IL-6-responsive regions of all three fibrinogen genes (10,33,34). This CTGG(G/ A)AA motif was also identified in the IL-6-responsive promoter region of the ␣ 2 -macroglobulin gene (35). Since the discovery of STAT3/APRF (36, 37), which interacts with a consensus element of TT(A/C)(C/T)N(G/A)(G/T)AA sequence, there has been intense effort to verify the role of the putative CTGG(G/A)AA motif and STAT3 in regulating the three fibrinogen genes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous several studies identified a highly conserved CTGG(G/A)AA motif in the IL-6-responsive regions of all three fibrinogen genes (10,33,34). This CTGG(G/ A)AA motif was also identified in the IL-6-responsive promoter region of the ␣ 2 -macroglobulin gene (35). Since the discovery of STAT3/APRF (36, 37), which interacts with a consensus element of TT(A/C)(C/T)N(G/A)(G/T)AA sequence, there has been intense effort to verify the role of the putative CTGG(G/A)AA motif and STAT3 in regulating the three fibrinogen genes.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear proteins of HepG2 cells were extracted as previously described [14]. A double-stranded synthetic oligonucleotide comprising the IL-6RE of the ICAM-1 promoter (upper strand: 5'-AGCTTAG-GTTTCCGGGAAAGCAC-3') was 32p-labelled by filling in the 5'-protruding ends with Klenow enzyme.…”
Section: Gel Retardation Analysismentioning
confidence: 99%
“…We have previously identified a ubiquitous transcription factor, APRF, which, in response to IL-6, transiently associates with gpl30 and then is tyrosine phosphorylated and translocated to the nucleus [12,14]. On the basis of immunological cross-reactivity and DNA-binding specificities we proposed a relationship of APRF to the interferon-),-activated transcription factor Stat 1 [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…STAT3 was initially identified as an acute phase response factor, an inducible DNA binding protein that binds to the IL-6 responsive element within the promoters of hepatic acute phase protein genes [13] . Subsequent studies indicate that STAT3 becomes activated in response to a wide variety of cytokines and growth factors [4,5,14] .…”
Section: Stat3 and Ibd Patientsmentioning
confidence: 99%